2022
DOI: 10.15243/jdmlm.2022.094.3773
|View full text |Cite
|
Sign up to set email alerts
|

Reclamation of a limestone quarry: effect of poultry manure and humic acid on the soil improvement

Abstract: Limestone processing produces dust covering the soil around the quarry site and may affect soil fertility. Post-mining activities in a forest area are mandatory to restore biodiversity, such as tree species of non-wood products. This study aimed to determine the impact of limestone dust on soil and measure the effectiveness of soil treatment for revegetation. This study employed a randomized block design with three soil groups, i.e. uncovered with limestone dust, covered with 2.5 cm limestone dust, and covered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Research conducted by Nurtyahani et al (2020) identified soil microorganisms to indicate soil quality, as the presence of microorganisms can serve as a medium for increasing nutrients. Another effort is a study by Yunanto et al (2022) aiming to influence the chemical properties of soil in former limestone mining areas by adding organic fertilizers from animal manure and poultry. Stephan et al (Stephan & Hubbart, 2022) showed that abandoned limestone mining land after one year, which lacks soil nutrients dominated by gravel content exceeding 60%, requires 70 years to restore plant succession in the mining area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research conducted by Nurtyahani et al (2020) identified soil microorganisms to indicate soil quality, as the presence of microorganisms can serve as a medium for increasing nutrients. Another effort is a study by Yunanto et al (2022) aiming to influence the chemical properties of soil in former limestone mining areas by adding organic fertilizers from animal manure and poultry. Stephan et al (Stephan & Hubbart, 2022) showed that abandoned limestone mining land after one year, which lacks soil nutrients dominated by gravel content exceeding 60%, requires 70 years to restore plant succession in the mining area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This can be due to the increased organic carbon content in the manure. Yunanto et al (2022) reported that manure can increase the C/N ratio, which can be beneficial for soil fertility. Therefore, the composition of manure plays an important role in the amount of C and N fractions in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…Manure from chicken manure is possible on the slopes of Mount Merapi because of its abundant availability. The method of giving chicken manure is one of the efforts that can improve and change the physical condition of the soil as a place to grow plants (Hilwa et al, 2020;Yunanto et al, 2022). Chicken manure fertilization is thought to boost production by enhancing the soil's physical, chemical, and biological qualities.…”
Section: Introductionmentioning
confidence: 99%